Low‐Coordination Single Au Atoms on Ultrathin ZnIn2S4 Nanosheets for Selective Photocatalytic CO2 Reduction towards CH4. (5th September 2022) - Si, Shenghe; Shou, Hongwei; Mao, Yuyin; Bao, Xiaolei; Zhai, Guangyao; Song, Kepeng; Wang, Zeyan; Wang, Peng; Liu, Yuanyuan; Zheng, Zhaoke; Dai, Ying; Song, Li; et al.
Abstract: Selective CO2 photoreduction to hydrocarbon fuels such as CH4 is promising and sustainable for carbon‐neutral future. However, lack of proper binding strengths with reaction intermediates makes it still a challenge for photocatalytic CO2 methanation with both high activity and selectivity. Here, low‐coordination single Au atoms (Au1 ‐S2 ) on ultrathin ZnIn2 S4 nanosheets was synthesized by a complex‐exchange route, enabling exceptional photocatalytic CO2 reduction performance. Under visible light irradiation, Au1 /ZnIn2 S4 catalyst exhibits a CH4 yield of 275 μmol g −1 h −1 with a selectivity as high as 77 %. As revealed by detailed characterizations and density functional theory calculations, Au1 /ZnIn2 S4 with Au1 ‐S2 structure not only display fast carrier transfer to underpin its superior activity, but also greatly reduce the energy barrier for protonation of *CO and stabilize the *CH3 intermediate, thereby leading to the selective CH4 generation from CO2 photoreduction. Abstract : Single Au atoms in Au1 ‐S2 low‐coordination structure on ultrathin ZnIn2 S4 nanosheets were prepared by a rational complex‐exchange route. Endowed with much faster interfacial electron transfer from [Ru(bpy)3 ]Cl2 photosensitizer and more appropriate binding strength with *CO intermediates, low‐coordination single Au atoms surpass Au nanoparticles counterpart in CO2 photoreduction, leading to CH4 product with both high activity and selectivity.